Assessment of technological and functional features of Lactiplantibacillus and Fructobacillus strains isolated from Opuntia ficus-indica fruits - Veron Ponce, Hernan Esteban (2023)
Opuntia ficus-indica fruits are outstanding for their sensory attributes and multiple health benefits. However, this fruit is highly perishable, and substantial efforts have been carried out to extend its shelf-life. Lactic fermentation of fruits by-products using autochthonous bacteria arises as relevant technology for preserving vegetables and their by-products. In this study, autochthonous Lactiplantibacillus plantarum and Fructobacillus fructosus strains previously selected from Opuntia ficus-indica fruits of Northwestern Argentina were characterized according to their technological and functional properties to select the most suitable for the production of fermented cactus pear products. L. plantarum strains showed better acidifying activity, decreasing the pH of the juice by about 2.9 units in 24 h. All the strains studied produced lactic and propionic acids, and L. plantarum S-811 and S-TF2 strains and F. fructosus S-TF7 strain were the better lactic acid producers, with values around 9.5 g/l. These strains also displayed antimicrobial activities against undesirable pathogen bacteria, showed a safety profile typical of lactic acid bacteria, and the juice fermented with these strains preserves the phenolic compounds content and antioxidant activity of unfermented juice. The obtained results showed the potential of L. plantarum S-811 and S-TF2, and F. fructosus S-22 for their use as starters for the fermentation of cactus pear by-products, standing out L. plantarum S-811 for its potentiality to elaborate a fermented cactus pear beverage. The cactus pear juice fermented by L. plantarum S-811 showed physicochemical and microbiological stability that favors juice shelf-life. Besides, fermentation conferred distinctive sensory features to the cactus pear juice without influencing consumers´ overall acceptability.